Healing Effect of Taila Dahana after Padana in Pilonidal Sinus (International Journal of Ayurveda and Pharma Research, 2023)
Pilonidal sinus is an epithelium lined tract, situated in sacrococcygeal region, containing hairs and unhealthy granulation tissue. The treatment includes both conservative and surgical procedures. It is highly recurrent in nature, which makes this condition more difficult to treat. In Ayurveda, it can be correlated with Salyaja nadivrana and treatment are Agnikarma (cautery), Eshana (probing), Padana (incision), Taila daha (cautery with oil) and Ksharasutra. Dahana (cautery) with Swarjikadi taila which is a type of Snigdha agnikarma (unctous cautery) after incision of pilonidal sinus tract as a one time procedure was done in a 29 year old male patient with pain, swelling and pus discharge from natal cleft. Healing was assessed by parameters like pain, granulation tissue and size of wound using grading method. Pain was much lesser, granulation tissue formation was normal and healing was improved in lesser time. The present study is to evaluate the healing effect of Dahana with Svarjikadi taila in pilonidal sinus after eshana and padana (full length incision of tract).